Isolation and Characterization of Biosurfactant-Producing Bacteria From Oil Well Batteries With Antimicrobial Activities Against Food-Borne and Plant Pathogens - Rani, Mamta; Weadge, Joel T.; Jabaji, Suha (Frontiers in Microbiology, 2020)
Microbial biosurfactants, produced by fungi, yeast and bacteria, are surface-active compounds with emulsifying properties that have a number of known activities, including the solubilization of microbial biofilms. In an on-going survey to uncover new or enhanced antimicrobial metabolite-producing microbes from harsh environments, such as oil-rich niches, 123 bacterial strains were isolated from three oil batteries in the region of Chauvin, Alberta, and characterized by 16S rRNA gene sequencing. Based on their nucleotide sequences, the strains are associated with 3 phyla (Actinobacteria, Proteobacteria and Firmicutes), as well as 17 other discrete genera that shared high homology with known sequences, with the majority of these strains identified to the species level. The prevalent strains associated with the three oil wells belonged to the Bacillus genus. Thirty-four of the 123 strains were identified as biosurfactant-producers, among which Bacillus methylotrophicus strain OB9 exhibited the highest biosurfactant activity based on multiple screening methods and a comparative analysis with the commercially available biosurfactant, Tween 20. B. methylotrophicus OB9 was selected for further antimicrobial analysis and addition of live cultures of B. methylotrophicus OB9 (or partially purified biosurfactant fractions thereof) were highly effective on biofilm disruption in agar diffusion assays against several Gram-negative food-borne bacteria and plant pathogens. Upon co-culturing with B. methylotrophicus OB9, the numbers of either Salmonella enterica subsp. enterica Newport SL1 or Xanthomonas campestris B07.007 cells significantly decreased after 6 h and were not retrieved from co-cultures following 12 h exposure. These results also translated to studies on plants, where bacterized tomato seedlings with OB9 significantly protected the tomato leaves from Salmonella enterica Newport SL1 contamination, as evidenced by a 40% reduction of log10 CFU of Salmonella/mg leaf tissue compared to non-bacterized tomato leaves. When B. methylotrophicus 0B9 was used for bacterized lettuce, the growth of X. campestris B07.007, the causal agent of bacterial leaf spot of lettuce, was completely inhibited. While limited, these studies are noteworthy as they demonstrate the inhibition spectrum of B. methylotrophicus 0B9 against both human and plant pathogens; thereby making this bacterium attractive for agricultural and food safety applications in a climate where microbial-biofilm persistence is an increasing problem.